Menganalisis Konsep Dasar Algoritma Genetika - Rizky Fatih Syahputra; Yahfizham Yahfizham (Universitas Palan, 2024)
Genetic algorithms are computer techniques inspired by the theory of evolution and genetics. Individual definition, chromosome initialization, chromosome testing, selection (crossover) and mutation are fundamental elements of genetic algorithms. Genetic algorithms are used to solve optimization problems, such as lesson planning, community services and traffic light adjustment. By producing the best combination of chromosomes, the genetic algorithm can achieve ideal results. The genetic algorithm produces appropriate planning data to avoid delays. This research uses the methods of data collection, individual definition and chromosome initialization. The result of this research is a service application designed to be able to plan efficiently through development using a genetic algorithm. Optimal planning occurs when processing planning data produces solutions that are efficient in terms of time, energy, and resources, and avoids conflicting schedules in the same place..